Characterization of Self-Assembly Complex Micelles Prepared from Casein and Keratin - Su, Xiao-Zhou; Wang, Hong-Ru (Asian Journal of Chemistry, 2014)
A novel amphiphilic complex micelles were developed utilizing self-assembly of casein and keratin in aqueous medium. The casein-keratin complex micelles were prepared in the pH ranges of 5.5-9.0 and became more stable and reinforced by the cross-linking effect of the transglutamianse. The formation of casein-keratin complex micelles was confirmed by dynamic light scattering, scanning electron microscope and atomic force microscopy. Results showed that the complex micelles near sphericity and there hydrodynamic diameters are 130-230 nm depending on the different mass ratio of casein to keratin and pH range. The structures of the complex micelles are more compact at low pH and looser at high pH. The complex micelles have the most compact structure at pH 7.5 with the mass ratio of casein to keratin is 2:1.